EVALUATION OF THE ELIMINATION EFFICENCY OF APPLE STEM GROOVING VIRUS BY DIFFERENT DETECTION METHODS - G.J. Hu; Y.F. Dong; Z.P. Zhang; X.D. Fan; F. Ren (Journal of Animal and Plant Sciences, 2024)
Apple stem grooving virus (ASGV) frequently occurs in apple trees and shows high sequence variability. Sensitive detection is essential for effective forecast and control of this viral disease. The reverse transcription-duplex polymerase chain reaction (RT-dPCR) was developed after screening of primer combinations, adjustment of annealing temperature, and optimization of dosage of primer pair combination and cDNA. Primer pair combination ASG-F3/R3-F4/R4 in reaction system 5 were screened to simultaneously detect two parts of the ASGV genome. Then, RT-dPCR and RT-regular PCR (RT-rPCR) were used to detect ASGV in regenerated apple plants after thermotherapy and in nature growing apple plants. The resutls showed that the detection efficiency of RT-dPCR was the same as the total of two RT-rPCRs. Moreover, RT-dPCR is a sensitive, rapid and simple method to detect ASGV from various apple plants. These findings might be useful in the prediction of viral disease incidence in host plants and this method can also be helpful to construct the same detection assays for other viruses.
Keywords: Apple stem grooving virus; Detection efficiency; RT-duplex PCR; Sensitivity; Various apple plants; V